Transport and health: a look at three Latin American cities - Janeth Mosquera Becerra; Rodrigo S. Reis; Lawrence D. Frank; Farah A. Ramirez-Marrero; Benjamin Welle; Eugenio Arriaga Cordero; Fabian Mendez Paz; Carlos Crespo; Veronica Dujon; Enrique Jacoby; Jennifer Dill; Lynn Weigand; et al. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
Transport is associated with environmental problems, economic losses, health and social inequalities. A number of European and US cities have implemented initiatives to promote multimodal modes of transport. In Latin America changes are occurring in public transport systems and a number of projects aimed at stimulating non-motorized modes of transport (walking and cycling) have already been implemented. Based on articles from peer-reviewed academic journals, this paper examines experiences in Bogotá (Colombia), Curitiba (Brazil), and Santiago (Chile), and identifies how changes to the transport system contribute to encourage active transportation. Bus rapid transit, ciclovias, bike paths/lanes, and car use restriction are initiatives that contribute to promoting active transportation in these cities. Few studies have been carried out on the relationship between transport and physical activity. Car ownership continues to increase. The public health sector needs to be a stronger activist in the transport policy decision-making process to incorporate health issues into the transport agenda in Latin America.